2017
DOI: 10.5935/2318-7670.v05n06a11
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrientes na serapilheira depositada em florestas secundárias no litoral do Paraná

Abstract: Os micronutrientes são muito importantes na manutenção da fertilidade do solo, sendo sua deposição via serapilheira em Floresta Atlântica ainda pouco estudada. Esse trabalho objetivou avaliar a concentração e o aporte de micronutrientes na serapilheira depositada em áreas secundárias da Floresta Ombrófila Densa Submontana em Antonina, PR. A serapilheira foi coletada em três parcelas em diferentes estágios de sucessão secundária, separada em frações e folhas de espécies conhecidas, seca e pesada para realização… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…(Rengel 2007). The micronutrient order in the litter (Fe > Mn > B > Zn > Cu) was similar for passive restoration sites, and have been corroborated by other tropical forests (Bianchin et al 2017;Klippel et al 2016;Lopez Hernandez et al 2014). After aluminum, iron is the second most abundant metal in the Earth's crust, possessing extremely low mobility (Broadley et al 2012).…”
Section: Effect Of Passive Restoration Age On Accumulated Litter Laye...supporting
confidence: 70%
See 1 more Smart Citation
“…(Rengel 2007). The micronutrient order in the litter (Fe > Mn > B > Zn > Cu) was similar for passive restoration sites, and have been corroborated by other tropical forests (Bianchin et al 2017;Klippel et al 2016;Lopez Hernandez et al 2014). After aluminum, iron is the second most abundant metal in the Earth's crust, possessing extremely low mobility (Broadley et al 2012).…”
Section: Effect Of Passive Restoration Age On Accumulated Litter Laye...supporting
confidence: 70%
“…There are few studies on micronutrient potential return. However, this study verifies that, the potential return of iron and manganese were lower than Dense Mountain Ombrophilous Forest (Freitas et al 2015), as well as Ombrophilous Dense Forest (Caldeira et al 2008) and Submontane Atlantic Rain Forest (advanced) (Bianchin et al 2017). Boron had shown to be lower than the values observed in Lowland (Sayer et al 2020) and Dense Mountain Ombrophilous Forest (Freitas et al 2015) but higher than Ombrophilous Dense Forest (Caldeira et al 2008).…”
Section: A Comparison Of Annual Nutrient Returns In Tropical Forestssupporting
confidence: 63%
“…The descending order of macronutrient (N > Ca > K > Mg > P > S) and micronutrient (Mn > Fe > B > Zn > Cu) concentration observed in the inselberg litterfall was the same for a fragment of Seasonal Deciduous Forest in the municipality of Itaara, Rio Grande do Sul state (Schumacher et al, 2018), and closed to that observed in litterfall from two sites of Alluvial Dense Ombrophilous Forest at different successional stages (Ca > N > K > Mg > P; Mn > Fe > Zn > Cu) in Salto Morato Natural Reserve, Paraná state (Scheer et al, 2011); the concentration of S and B were not determined in the referred study. Regarding specifically the concentration of micronutrients, the decreasing order was also very similar in comparison with the litterfall of areas of Submontane Dense Ombrophilous Forest (Mn > Fe > Cu > Zn), regardless of the successional stage (initial, intermediate, advanced), in the Guaricica Natural Reserve, Paraná state (Bianchin et al, 2017).…”
Section: Discussionmentioning
confidence: 61%
“…The data were individualized in seasons (spring: September, October, and November; summer: December, January, and February; autumn: March, April, and May; winter: June, July, and August), following the methodology of other studies (Bianchin et al, 2017). The interaction effects between season (spring, summer, autumn, winter) and litterfall fraction (PP, OS) were investigated within five pseudo-replicates for both litterfall and C content, and three pseudo-replicates for nutrient concentration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation